In vitro antioxidant and anticancer activities of Clinacanthus nutans extracts - Hui Yie Phung, Joyce; Lim Fong, Isabel; Yen Khong, Heng; Kit Ban, Weng (Science, Engineering and Health Studies, 2021)
Clinacanthus nutans (CN), from the Acanthaceae family is a medicinal plant widely used in Thailand and Malaysia. CN is commonly used as a treatment of inflammation, cancer, and herpes virus infection. This study aimed to determine the antioxidant activity and anticancer properties of CN leaves extracts on human colorectal cancer cell lines, HCT 116 and HT-29. In this study, CN leaves powders were extracted in methanol, chloroform, and acetone at different durations. The crude extracts were assessed for total phenolic content (TPC), total flavonoid contents (TFC), 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity and MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) tetrazolium reduction assay. The extract using acetone showed with the highest TPC. The highest total flavonoid content was the methanol extract. The DPPH radical scavenging activity, IC50 of methanol extract was 19.67 µg/mL and exhibited the most efficacious antioxidant property among the others. The 24-hour methanol extract showed the most promising results on MTT assay. Therefore, CN methanol extract is a promising candidate to proceed in other anticancer studies such as cell cycle arrest and apoptosis assays.